DETERMINATION OF ENERGY NEEDS OF KU-IV SWIMMING ATHLETES AT THE KRAKATAU ATLANTIC SWIMMING ASSOCIATION (PRKA) SWIMMING CLUB - Asih Setyo Rini; Ahmad Padhil; Asep Rahmatullah; Dedy Khaerudin (Journal of Industrial Engineering Management, 2023)
Swimming is an aquatic sport in which almost all members of the body require coordination of motion. Not only that, but swimming also includes sports that are programmed for achievement by competing at speed, both short, medium, and long distances. The Krakatau Atlantic Swimming Association (PRKA Swimming Club) is one of the first and oldest swimming clubs in Cilegon which was formed on July 7, 1990. This association is chaired by Drs. Zuladri Firman. The training program is held six times per week: Tuesday, Thursday, and Saturday at 16.00 – 17.45 WIB and Monday, Wednesday, and Friday at 05.00 – 06.30 WIB. On Sundays, ground or physical training is carried out at 07.00 – 09.00 WIB. Age group (KU) IV athletes to achieve maximum performance, need an optimal training system and appropriate energy requirements. Based on the calculation results, the average energy requirement for KU-IV athletes is 1.64 kcal/minute.